2006
DOI: 10.1161/01.str.0000209238.61459.39
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion-CT Assessment of Infarct Core and Penumbra

Abstract: Background and Purpose-Different definitions have been proposed to define the ischemic penumbra from perfusion-CT (PCT) data, based on parameters and thresholds tested only in small pilot studies. The purpose of this study was to perform a systematic evaluation of all PCT parameters (cerebral blood flow, volume [CBV], mean transit time [MTT], time-to-peak) in a large series of acute stroke patients, to determine which (combination of) parameters most accurately predicts infarct and penumbra. Methods-One hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
360
4
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 698 publications
(375 citation statements)
references
References 16 publications
8
360
4
3
Order By: Relevance
“…[22] Our quantitative perfusion values were within the range described by other groups. [17,23] Also, our semiquantitative analyses were in the same line as the quantitative findings, which further supports the validity of our quantitative measures.…”
Section: Discussionsupporting
confidence: 83%
“…[22] Our quantitative perfusion values were within the range described by other groups. [17,23] Also, our semiquantitative analyses were in the same line as the quantitative findings, which further supports the validity of our quantitative measures.…”
Section: Discussionsupporting
confidence: 83%
“…Our results suggesting that the MTT is indeed a reasonably reliable surrogate of the penumbra flow threshold provide support to time-based perfusion mapping using MR or CT in the clinical setting-provided appropriate stringent thresholds are used (Donnan et al, 2009). As with MR, the diffusion weighted imaging lesion may represent not only the core but also the penumbral tissue (Guadagno et al, 2006), whereas with CT perfusion, there are inconsistencies regarding a CBV threshold for the core tissue (Murphy et al, 2008;Wintermark et al, 2006), clinically reliable maps of the penumbra and core compartments are still awaited. Defining reliable core markers is therefore an important issue to address in future work.…”
Section: Discussionmentioning
confidence: 63%
“…Our AUCs were overall lower than the former, but higher than the latter two pMR studies. The fourth study, based on pCT (Wintermark et al, 2006), reported an inordinately high AUC of 0.96 for the MTT ratio. Overall, therefore, the AUCs found in this study are well within the range reported in earlier pMR or pCT studies, in turn further supporting the validity of MTT for predicting the penumbra flow threshold.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations